Effectiveness of Convergent Mastery Technique in Teaching Selected Topics in High School Trigonometry - Sucuano, Jean V. (JPAIR Institutional Research, 2014)
Trigonometry as a subject can be difficult to comprehend especially on proving identities and solving trigonometric functions. It is important that a teacher must incorporate a teaching style which could help students better comprehend the subject. Convergent mastery technique is a recommended technique for better mastery and comprehension. To provide empirical facts on the effect of convergent mastery technique in teaching Trigonometry to junior-high-school students, this study was conducted. This study used a quasi-experimental design called the pre-test-post-test control design. The participants were the two heterogeneous sections of the third-year level of Stella Maris Academy of Davao. The tool in this study used is a 40-item teacher-made test with 17 items for the topic "The Fundamental Trigonometric Identities" and 23 items for the topic "Verifying Trigonometric Identities" This instrument was used in the pre-test and post-test to measure the achievement of the students both in the experimental and the control group. The data gathered were summarized, translated, and analyzed using the mean scores for both pre-test and post-test. At 0.05 level of significance, the t-test was used to find a significant difference between the experimental and control groups. Findings show the significant difference between pre-test and post-test scores as well as the mean gain scores of the two groups. Thus, convergent mastery technique is an operational strategy in improving the academic achievement of students and is recommended to be used in teaching mathematics or in any discipline.
Keywords: Mathematics Education; effectiveness of convergent mastery technique; high school trigonometry; quasi-experimental design; Davao City; Philippines